Law Enforcement on Blasphemy Offense (Study case on Lia Eden Community, Yusman Roy and Ahmadiyah ) - Saru Arifin (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2008)
This research attempts to analyze the argumentations or factors which are used by government to criminalize heretical sects in Indonesia and their relation to the freedom to perform devotional acts in accordance with one’s religion or belief. This is a normative-juridical research, under the consideration that the standpoint of the research merely analyzes laws and regulations on heretical sects. However, the library research has been conducted not only on laws and regulations in Indonesia but also some legal provisions on blasphemy from many other countries. Based on the analysis in this research, the result shows that parameter used by the government to criminalize the adherents of the heretical sect in Indonesia refers to the provision article 156b KUHP. The three cases studied in this research are Lia Eden, Yusman Roy and Ahmadiyah, proven to commit blasphemy. To support the argumentation of article 156a, the panel of judges confirmed various evidence including the opinion of the pre-requested qualified expert of religion.Keywords: blasphemy, law, belief, and human rights.